2004
DOI: 10.1377/hlthaff.23.5.113
|View full text |Cite
|
Sign up to set email alerts
|

Did A Rising Tide Lift All Boats? The NIH Budget And Pediatric Research Portfolio

Abstract: This paper examines National Institutes of Health (NIH) pediatric research spending in absolute terms and relative to the doubling of the NIH overall budget between fiscal years 1998 and 2003. Pediatric spending increased by an average annual rate of 12.8 percent during the doubling period (almost on par with the NIH average annual growth rate of 14.7 percent). However, the proportion of the total NIH budget devoted to the pediatric portfolio declined from 12.3 to 11.3 percent. We offer recommendations for imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Using a web-based search of funding organizations in the UK, Hawkins et al have found that the overall proportion of funding devoted to children is approximately 3%, and even lower proportions of funding are devoted to government priorities such as health inequality and adolescent services [4]. By comparison the National Institutes for Health in the United States devotes only about 11-12% of its budget to pediatrics [5]. It may also be asked whether the rise in number of articles might correlate with manpower shifts in pediatric and adult ORL, and whether the increase in number of articles mirrors an increasing workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Using a web-based search of funding organizations in the UK, Hawkins et al have found that the overall proportion of funding devoted to children is approximately 3%, and even lower proportions of funding are devoted to government priorities such as health inequality and adolescent services [4]. By comparison the National Institutes for Health in the United States devotes only about 11-12% of its budget to pediatrics [5]. It may also be asked whether the rise in number of articles might correlate with manpower shifts in pediatric and adult ORL, and whether the increase in number of articles mirrors an increasing workforce.…”
Section: Discussionmentioning
confidence: 99%
“…5 The NICHD was designated as the lead institute on a number of the initiatives, including establishment of a pediatric research initiative (PRI), expansion of autism-related and Fragile X syndrome research activities, and conducting a national longitudinal study of environmental influences on child health (National Children' Study or "NCS"). 6 Congress established the PRI to increase support for pediatric research, enhance collaborative efforts among ICs, speed the development of pediatric clinical drug trials, and invest in training pediatric researchers through a loan repayment program. Because a major component of the longstanding mission of the Eunice Kennedy Shriver NICHD is to improve and promote children's health and development, the NIH Director requested the NICHD Director to oversee and coordinate the PRI at the NIH and to coordinate preparation of the annual report on the status of the pediatric research portfolio (new and continuing grants and contracts).…”
Section: Methods Data and Policy Significancementioning
confidence: 99%
“…With a specific interest in the status of the federal pediatric research portfolio, Gitterman et al (2004) reported on trends in pediatric research funding in absolute terms and relative to the NIH budget, with a specific focus on the doubling period [fiscal year (FY) 1998 -2003] when congressional appropriations increased from $13.6 billion to $27.1 billion. The intent in this report was to avoid interpreting funding as a competition between diseases that impact children versus adults but to report on how the NIH pediatric research portfolio fared in comparison with the overall budget during the doubling era (6).…”
mentioning
confidence: 99%
“…27 Addressing whether existing resources will be enough to address the gaps in children's health care science that impede improving children's health outcomes is beyond the scope of this commentary. Given longstanding concerns about the resources available for pediatric research, [28][29][30] more in-depth analysis could be helpful and lead to a prioritized clinical research agenda in child health. 6 Setting research priorities can be a difficult topic given the variety of criteria, but several approaches are emerging and could be adapted for use within the translational continuum.…”
Section: S92mentioning
confidence: 99%